Implementation of Community Service-Based Indonesian Learning at UINSI Samarinda - Nur Syamsi; Heriyanti Heriyanti (Southeast Asian Journal of Islamic Education, 2022)
The 5.0 society is a challenge in the world of education. Not only technological advances but the value of humanity must also be upheld. Teachers or lecturers as educators who try to improve the nation’s life should have a great responsibility. Lecturers must realize students can still be competitive in accordance with the era without ignoring humanist values. One of the efforts that can be done is to make innovations in learning. Learning innovation can be done on the media or learning methods used. In this study, researchers tried to innovate learning from the aspect of learning methods. Researchers implemented community service-based Indonesian learning, which is expected to build students' humanist characters and problem-solving ability in community life. This research was qualitative. Data collection was done by researchers as the main instrument that involves directly in the field. Therefore, this research was categorized as field research. Data collection techniques were carried out using observation, interviews, and documentation. The data collected was analyzed using condensation, display, and conclusion drawing. The results showed that community service-based Indonesian learning could be done through five stages, namely: FGD stage, planning stage, socialization stage, learning implementation stage, and reflection and evaluation stage. Each stage consists of several steps of the activity, output, and the values obtained. This learning activity can be applied in various other courses, especially science related to humanities studies.